A Case Study Of Top Lordotic Chest Radiography Examination In Tuberculosis Cases At The Radiology Installation Of Universitas Gadjah Mada Academic Hospital - Zalfa Zahirah Indrawiguna; Asih Puji Utami; Sofie Nornalita Dewi (International Journal of Social Science, 2026)
Background: Pulmonary tuberculosis is a serious global health problem, with Indonesia ranking second worldwide for the highest case burden. Mycobacterium tuberculosis tends to colonize the lung apex; however, standard AP/PA projections present limitations due to clavicle superimposition, which creates a diagnostic blind spot. Current literature recommends an apical lordotic projection with a 15°-20° cephalad angulation, but its application in clinical settings is often adjusted to the patient's condition, resulting in angle variations that have not been scientifically evaluated. This study aims to analyze the 35° top lordotic chest technique and evaluate its diagnostic image value in tuberculosis cases at the Radiology Installation of RSA (Academic Hospital) UGM. Methods: This qualitative descriptive case study was conducted at the Radiology Installation of UGM Academic Hospital from February to May 2026. The subjects consisted of three radiographers and one radiologist, selected through purposive sampling. Data were collected via observation, semi-structured interviews, and PACS image documentation. The data were analyzed using the interactive model by Miles et al. (2014), encompassing thematic analysis, data display, and conclusion drawing/verification, utilizing source triangulation. Results: This technique was applied using an erect true AP position, a central ray of 35° cephalad, a central point at the manubrium sterni, 58 kVp, 8 mAs, and a 150 cm SID. It was utilized as a compensatory method for patients unable to perform an active lordotic position. The resulting images demonstrated bilateral lung apices free of clavicle superimposition, revealing infiltrates, consolidation, and fibrotic lines in the suprahilar, perihilar, and bilateral paracardial regions, suggesting bilateral pneumonia without ruling out TB. The radiologist affirmed that this technique provides clinical added value for the visualization of apical lesions. Conclusion: This technique serves as a rational clinical adaptation to patient limitations and produces images with adequate diagnostic value for evaluating the lung apex. It is recommended as a complementary examination, rather than a replacement for standard PA/AP projections. The definitive confirmation of tuberculosis still necessitates clinical correlation and ancillary tests, such as Acid-Fast Bacilli (AFB) sputum smears or cultures.